Integrated coastal zone management in the context of COVID-19. (1st September 2021) - Perillo, Gerardo M.E.; Botero, Camilo M.; Milanes, Celene B.; Elliff, Carla I.; Cervantes, Omar; Zielinski, Seweryn; Bombana, Briana; Glavovic, Bruce C.
Abstract: With the increasing need for and emergence of research on ocean and coastal issues in the context of the COVID-19 pandemic, the Ocean & Coastal Management journal presents this Special Issue with relevant articles within the scope of Coastal Management in times of COVID-19. This Special Issue received 43 tentative abstracts, 29 manuscripts were submitted, and finally, 12 articles were accepted. We provide a wide panorama of those twelve articles that integrate the special issue, covering a diverse range of topics regarding coastal management in the COVID-19 pandemic. Seven papers are studies that discuss environmental and social problems during this time in coastal zones, while the other five explore the use of technology to face COVID-19 on beaches. These twelve articles give some insights to improve coastal management, focused on tourist beaches, natural disasters, and fisheries. In sum, this special issue offers an organized compendium of high-level articles, as a contribution to evolve towards the better ocean and coastal management within the rapid emerging of publications about COVID-19. Highlights: Role of science within these times of uncertainty by COVID-19. We provide a panorama of twelve articles that integrate the special issue. COVID-19 affected tourism activity and beach management in Latin America. Current studies applied worldwide regarding coastal management in the COVID-19 pandemic.